MUTU LAYANAN PENDIDIKAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI PONDOK PESANTREN TAHFIDZUL QUR’AN AISYIYAH BAKI (KHUSUS PUTRI) TAHUN PELAJARAN 2024/2025 - ARIF HABIBIR RAHMAN (UNISAN JURNAL, 2025)
Aisyiyah Baki Tahfidzul Qur’an Islamic boarding school is an educational institution committed to enhancing the quality of education for its students, especially for female students. This study aims to analyze the quality of educational service provided at this boarding school and its impact on the educational quality received by female students. Using a qualitative research methodology, data were collected through interviews, observations, and documentation. The findings indicate a significant improvement in educational quality, measured through student satisfaction, academic achievements, and character development indicators. However, challenges remain regarding facilities and human resources that need to be addressed. Thus, strengthening the quality of educational services is key to achieving a better educational vision in the pesantren and enhancing the contributions of female students to society.